Effect of marker-free transgenic Chlamydomonas on the control of Aedes mosquito population and on plankton - Xiaowen Fei; Xiaodan Huang; Zhijie Li; Xinghan Li; Changhao He; Sha Xiao; Yajun Li; Xiuxia Zhang; Xiaodong Deng (Parasites & Vectors, 2023)
Abstract Background More than half of the world’s population suffers from epidemic diseases that are spread by mosquitoes. The primary strategy used to stop the spread of mosquito-borne diseases is vector control. Interference RNA (RNAi) is a powerful tool for controlling insect populations and may be less susceptible to insect resistance than other strategies. However, public concerns have been raised because of the transfer of antibiotic resistance marker genes to environmental microorganisms after integration into the recipient genome, thus allowing the pathogen to acquire resistance. Therefore, in the present study, we modified the 3-hydroxykynurenine transaminase (3hkt) and hormone receptor 3 (hr3) RNAi vectors to remove antibiotic resistance marker genes and retain the expression cassette of the inverse repeat sequence of the 3hkt/hr3 target gene. This recombinant microalgal marker-free RNAi insecticide was subsequently added to the suburban water in a simulated-field trial to test its ability to control mosquito population. Methods The expression cassette of the 3hkt/hr3 inverted repeat sequence and a DNA fragment of the argininosuccinate lyase gene without the ampicillin resistance gene were obtained using restriction enzyme digestion and recovery. After the cotransformation of Chlamydomonas, the recombinant algae was then employed to feed Aedes albopictus larvae. Ten and 300 larvae were used in small- and large-scale laboratory Ae.albopictus feeding trials, respectively. Simulated field trials were conducted using Meishe River water that was complemented with recombinant Chlamydomonas. Moreover, the impact of recombinant microalgae on phytoplankton and zooplankton in the released water was explored via high-throughput sequencing. Results The marker-free RNAi-recombinant Chlamydomonas effectively silenced the 3hkt/hr3 target gene, resulting in the inhibition of Ae. albopictus development and also in the high rate of Ae. albopictus larvae mortality in the laboratory and simulated field trials. In addition, the results confirmed that the effect of recombinant Chlamydomonas on plankton in the released water was similar to that of the nontransgenic Chlamydomonas, which could reduce the abundance and species of plankton. Conclusions The marker-free RNAi-recombinant Chlamydomonas are highly lethal to the Ae. albopictus mosquito, and their effect on plankton in released water is similar to that of the nontransgenic algal strains, which reduces the abundance and species of plankton. Thus, marker-free recombinant Chlamydomonas can be used for mosquito biorational control and mosquito-borne disease prevention. Graphical Abstract